CircB3GNTL1 and miR-598 regulation effects on proliferation, apoptosis, and glutaminolysis in gastric cancer cells - Ye, Bin; Yu, Shan; Wang, Jingang; Ren, Yuhan (Cellular and Molecular Biology, 2020)
This study was performed to research circB3GNTL1 control, miR-598 and its mechanism for cell proliferation, apoptosis and glutamine breakdown. For this purpose, CirB3GNTL1 and miR-598 expressions were detected by qRT-PCR in gastric and cell lines; MTT tests were performed to detect proliferation; flow cytometry was established in flow; glutamine decomposition was evaluated with glutamine, glutamic acid and Î±-keto-glutaric acid (Î±-KG) expression; Bcl-2, PCNA, ASCT2 and GLS1 expression levels were calculated; Methods of expression were calculated. The results showed that CircB3GNTL1 expression was up-regulated and miR-598 expression was up-regulated in gastric cancer tissues and cell lines; Knockdown circB3GNTL1 prevented proliferation and glutamine decomposition of the gastric cancer cells and induced apoptosis compared with normal para-cancers and gastric cancer cell lines. Results circB3GNTL1 can target and control miR-598 expression, and miR-598 can reverse the proliferation, apoptosis, and decomposition of glutamine from gastric cancer cells by knockdown circB3GNTL1. It was concluded that CirB3GNTL1 prevents decomposition of glutamines and induces apoptosis by controlling miR-598 in gastric cancer cells.